2007
DOI: 10.1007/s11244-006-0139-x
|View full text |Cite
|
Sign up to set email alerts
|

Absolute potential measurements in solid and aqueous electrochemistry using two Kelvin probes and their implications for the electrochemical promotion of catalysis

Abstract: The concept of absolute electrode potential in aqueous and solid electrochemistry is discussed in light of the first experimental investigation utilizing a two Kelvin probe system which allows for direct in situ measurement of the work functions of both the, emersed or spillover modified, working and reference electrodes.In both cases, i.e. emersed electrodes in aqueous electrochemistry and spillover-modified electrodes in solid electrochemistry, it is found that the following two equations relate the working-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Notice on the other hand, that although the pzc is highly sensitive to particular experimental conditions, our value is in better agreement with the value of −0.70 eV, recently reported [48]. Moreover, the absolute electrochemical potential U abs of the system presented here is similar to the work function of Cu upon water layer adsorption as well, which Tsiplakides et al [27] have found to be −4.64 V for an emersed rotating electrode surface that corresponds to a Daniel cell and −4.80 V obtained from a 0.1 M LiOH solution. Figure 8 shows the averaged electrochemical energy profiles.…”
Section: Electrochemical Potentialssupporting
confidence: 92%
See 1 more Smart Citation
“…Notice on the other hand, that although the pzc is highly sensitive to particular experimental conditions, our value is in better agreement with the value of −0.70 eV, recently reported [48]. Moreover, the absolute electrochemical potential U abs of the system presented here is similar to the work function of Cu upon water layer adsorption as well, which Tsiplakides et al [27] have found to be −4.64 V for an emersed rotating electrode surface that corresponds to a Daniel cell and −4.80 V obtained from a 0.1 M LiOH solution. Figure 8 shows the averaged electrochemical energy profiles.…”
Section: Electrochemical Potentialssupporting
confidence: 92%
“…Concerning the electrochemical potential, we can start with the work of Tsiplakides et al [27] who determined the potential of zero charge (pzc) for Cu on emersed rotating electrodes. In their study they also confirmed experimentally that the choice of a reference point above the emersed electrode coincides with the reference point at infinity for overall uncharged cells.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In nanotechnology the adsorption of organic layers onto metal surfaces is widely used as a method for the work function manipulation of metal electrodes in order to achieve electron transport in organo-electronic devices. [9][10][11][12][13][14] Several effects may influence the interfacial dipole moment of an organic film on a metal surface, responsible for the shift of metal work function: a dipole moment of organic molecules in the film, which is determined by the dipole moment of an isolated molecule and the molecule's charge rearrangement due to intermolecular interactions in the film, the charge transfer between the molecules and the metal leading to the formation of an additional dipole at the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Potential drop across the head-and tail-group capacitors and the total shift of the work function of Au surface by the chemisorbed monolayer of S(CH 2 ) 11 COOH molecules, calculated using Equation 2, DW(2) , and Equation 1, DW(1) .…”
mentioning
confidence: 99%
“…9), as the prevailing part of inner or Galvani potential (∆φ). Namely, Vayenas et al [24,25] have proved on plentiful systems in solid state electrolyte [26], aqueous media [27-29,] and PEM Nafion 112 [30] the basic NEMCA or EPOC promotion relation in heterogeneous catalysis, Φ e U WR    (14) that could also be considered as fundamental both in electrode kinetics [31][32][33] and spillover phenomena [34]. Meanwhile, the latter (Eq.…”
Section: ∆μ (M-oh) = E∆χmentioning
confidence: 99%